Production of 18F‐Labeled Titanium Dioxide Nanoparticles by Proton Irradiation for Biodistribution and Biological Fate Studies in Rats. (4th November 2013) - Pérez‐Campaña, Carlos; Sansaloni, Francesc; Gómez‐Vallejo, Vanessa; Baz, Zuriñe; Martin, Abraham; Moya, Sergio E.; Lagares, Juan I.; Ziolo, Ronald F.; Llop, Jordi
<x xml:space="preserve">Abstract</x> A simple and straightforward method is presented for the direct proton beam activation of 18O‐enriched titanium dioxide nanoparticles (TiO2 NPs) via the 18O(p, n)18F nuclear reaction in order to assess the biological fate of the NPs using positron emission tomography (PET). The radiolabeling of the NPs does not alter their morphological properties as demonstrated by transmission electron microscopy and dynamic light scattering measurements. The simultaneous formation of other radioisotopes by activation of the titanium atom, i.e., 48V, 47V, 44gSc, has been investigated using high‐resolution gamma spectrometry and PET. The labeling of TiO2 NPs with radioactive 18F atoms makes it possible to perform short‐term in vivo biodistribution studies of the metal oxide NPs in rats after intravenous and oral administration using PET. The accumulation of NPs in different organs could be quantified during almost 8 h after administration.